Nitrones as trapping reagents of α,β-unsaturated carbene intermediates - (1,2)Oxazino (5,4-b)indoles by a platinum-catalyzed intermolecular (3+3) cycloaddition - Yang, Weibo; Wang, Tao; Shi, Shuai; Zhang, Tuo; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2013)
Some readily available Boc-protected 2-(3-methoxy-1-propynyl)anilines and nitrones in platinum-catalyzed reactions deliver [1,2]oxazino[5,4-b]indoles. Twelve examples with yields of 41-95% are reported. Different substituents like nitro, trifluoromethyl, fluoro, bromo, and ester groups are tolerated. With regard to the mechanism, this reaction probably combines an initial intramolecular cyclization/elimination to vinylcarbenoid species and a subsequent stepwise intermolecular [3+3] cycloaddition with the nitrones.